DETEKSI TUMPAHAN MINYAK DI TELUK BALIKPAPAN TAHUN 2018 MENGGUNAKAN CITRA SENTINEL 1A - Mohammad Tri Arwadi; Iwan Suyatna; Widya Kusumaningrum (Jurnal Tropical Aquatic Sciences, 2022)
Indonesia has strategic shipping lanes and abundant natural resources, one of them is petroleum. These conditions is an advantage for Indonesia, but also it give challenges for the around ecosystem. In March 2018 there was oil spill accident in Balikpapan Bay. This incident brought bad impact for ecosystem around and people too. Based on these the research set out to monitoring the direction of distribution oil spill, the method can use remote sensing technology to search it with Sentinel 1A imagery. The image analysis used thresholding digital number. The results obtained the direction oil spill is spread out to east direction in area about ±82.579 km2 (01 April 2018). While on 13 April 2018 the oil spill there was still covering area about ±​​26,896 km2.